In Vitro Neutralisation Sensitivity of Gold (I) and Bismuth (III) Thiolates against Human Immunodeficiency Virus Type 1 virus-like particles - Liew, Li Yuan * (2024)
Human immunodeficiency virus type 1 (HIV-1) infects immune cells, causing one to experience immunodeficiency. The high prevalence of HIV-1 infections around the globe makes them the major public health issue. Anti-retroviral drugs (ARVs) are prescribed as treatment for HIV-1 infected individuals, yet the choices of effective ARVs become limited due to the rise of drug resistance. Therefore, the first objective of this study is to identify possible binding target of gold thiolates, specifically as entry inhibitors, through in silico analysis; and the second objective is to unveil potential anti-HIV-1 activities of gold thiolates as well as bismuth thiolates (hereon define as AAu and Bis complexes) against viral replication and viral entry. Physical binding abilities of complexes to HIV-1 viral proteins were screened using ELISA assay. Complexes were added to recombinant viral proteins, but no interaction was found between the complexes and the recombinant proteins tested. In spite of that, AAu and Bis complexes exhibited in vitro anti-HIV-1 activities in bioassays that involves the use of virus-like particles (VLPs). HIV-1 VLPs were produced from transient transfection of HEK293T cells with HIV-1 encoding luciferase reporter vectors and Env-expressing plasmids. By exposing HEK293T cells to treatments before or after transfection, AAu3, AAu2, Bis2, and Bis3 resulted in reduced level of viral protein expressed and/or decreased viral infectivity, thus suggesting their effects against viral replication with the following mechanisms of actions: (1) AAu2 and AAu3 disrupts the formation of functional VLPs; and (2) Bis2 and Bis3 affect the overall viral protein expression. In addition to viral replication, inhibitory effects of AAu and Bis complexes against the entry of HIV-1 VLPs were evaluated by treating VLPs before infecting Cf2Th.CD4.CCR5 cells that are permissive to infections of HIV-1 virions and VLPs. All complexes demonstrated significant neutralising activities against HIV-1 strains (strain BG505.W6M.C2, JR-FL, WTO.33, ZM197 and CM246.c1) with IC50 values ranged between 0.6 µg/mL and 6.13 µg/mL. The neutralising properties of AAu complexes were supported by the in silico docking studies that revealed their potential interacting site on HIV-1 Env trimer. AAu1 – 3 bind similarly to inner domain of Env trimer, demonstrating binding affinities from -7.34 kcal/mol to -7.62 kcal/mol. The interacting site shared among AAu complexes lies within the interface of gp120 and gp41 subunits, a site that play major role in regulating subunit gp120-gp41 association and CD4-gp120 association. Based on the in vitro neutralisation assays and docking studies, AAu and Bis complexes are suggested as potential entry inhibitors due to their significant neutralizing activities against HIV-1 VLPs, more notably AAu with a proposed mechanism in which the conformational shifting of Env is intervened.